2020
DOI: 10.1002/anie.202002394
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Superior Electrocatalytic Performance by Surface Copper Vacancy Defects during Electrochemical Etching Process

Abstract: Vacancy defects of catalysts have been extensively studied and proven to be beneficial to various electrocatalytic reactions. Herein, an ultra‐stable three‐dimensional PtCu nanowire network (NNW) with ultrafine size, self‐supporting rigid structure, and Cu vacancy defects has been developed. The vacancy defect‐rich PtCu NNW exhibits an outstanding performance for the oxygen reduction reaction (ORR), with a mass activity 14.1 times higher than for the commercial Pt/C catalyst (20 %.wt, JM), which is currently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 42 publications
8
93
0
Order By: Relevance
“…In FT-EXAFS spectra of Au L 3 -edge, the peak intensity of np-Cu 1 Au SAA is lower than that of Au foil and np-Au (Fig. 2c), which suggests the formation of lowcoordination Au-Au/Cu defect sites [34,35]. Furthermore, we found that the absorption edge of np-Cu 1 Au SAA is located between the Cu foil and CuO (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…In FT-EXAFS spectra of Au L 3 -edge, the peak intensity of np-Cu 1 Au SAA is lower than that of Au foil and np-Au (Fig. 2c), which suggests the formation of lowcoordination Au-Au/Cu defect sites [34,35]. Furthermore, we found that the absorption edge of np-Cu 1 Au SAA is located between the Cu foil and CuO (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…With the reduction of the total noble metals (Pt and Pd) as a key emphasis of the catalyst design while harnessing the above attributes, the third metal, M′, a non-noble transition metal (e.g., Cu, Co, Ni, Fe, etc. ), plays a central role in the catalytic synergy by alloying with the noble metals reflected by optimization of both electronic and strain effects, as known for simple bimetallic systems, e.g., PtCu 31 , and PdCu 32 . Another important consideration of the ternary catalyst design is the exploitation of the increased entropy effect, which is well known to homogenize the compositions towards maximum randomness or remove phase segregation for enhancing corrosion resistance 33 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 25–30 ] Its structure and its catalytic activity of the shell are revealed to be highly dependent on the used core. [ 31–34 ] This is because the strain effect (expansion or compression) can be effectively controlled, up to the difference of intrinsic lattice parameters between the core and the shell. [ 34–41 ] For example, an expanded strain increases the d‐band center of the active shell, resulting in strengthened adsorption of ethanol and OH species, and eventually much facilitated ethanol electro‐oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Its structure and its catalytic activity of the shell are revealed to be highly dependent on the used core. [31][32][33][34] This is because the strain effect (expansion or compression) can be Direct alcohol fuel cells (DAFCs) utilize alcohol electro-oxidation reactions (AORs) to provide electricity, where catalysts with optimal electronic structures are required to accelerate sluggish AORs. Herein, an electrocatalyst with an Au-nanorod core and a PdPt-alloy shell is designed.…”
mentioning
confidence: 99%